Enhanced cycling performance of Li ion batteries based on Ni-rich cathode materials with LaPO4/Li3PO4 co-modification. Issue 24 (15th December 2021) - He, Rui; Wei, Aijia; Bai, Xue; Zhang, Lihui; Li, Xiaohui; Jinping Mu; Zhang, Xi; Ge, Jianmin; Liu, Zhenfa
Abstract: The recent development of Li-ion batteries based on Ni-rich cathodes with high specific capacity has generated considerable interest. However, cathodes with a sufficiently high Ni concentration suffer from rapid capacity decay and poor thermal stability during charge/discharge cycling, which represents a substantial challenge toward commercialization. While the application of a coating layer has been demonstrated to be an effective means of solving this issue, this typically increases the complexity and expense of cathode material fabrication. The present work addresses this issue by applying a LaPO4 /Li3 PO4 (LP) layer on the surface of LiNi0.83 Co0.11 Mn0.06 O2 cathode materials using a facile in situ coating method. This simple method functions concurrently with the high-temperature solid-state method employed for fabricating the cathode materials using Ni0.83 Co0.11 Mn0.06 (OH)2 as a precursor with added ammonium dihydrogen phosphate (NH4 H2 PO4 ) and lanthanum nitrate (La(NO3 )3 ). The modified cathode material reacts with residual Li, and forms a LP layer on the Ni-rich cathode surface, while a proportion of the La 3+ diffuses into the layered LiNi0.83 Co0.11 Mn0.06 O2 structure during the modification process. Experimental investigation indicates that the LP layer not only eliminates the residual Li, but also deters the formation of microcracks, and thereby inhibits reactions with the electrolyte during charge/discharge cycling. The LP-modified LiNi0.83 Co0.11 Mn0.06 O2 sample is demonstrated to attain a capacity retention of 94% and 79.8% after 100 and 500 charge/discharge cycles conducted at 1C, respectively.